2020
DOI: 10.3390/app10041407
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of the Fluid Mixture Confined by a Semipermeable Membrane: A Density Functional Study

Abstract: Classical density functional theory (DFT) is employed to study the structural properties of a binary fluid mixture confined by a semipermeable membrane. The influences of volume fraction and size asymmetry on three characteristic densities and excess adsorption are investigated in detail. In addition, some of our results are calculated by the analytical method, which agree well with those from the DFT calculations. These results may provide helpful clues to understand the structural properties of other complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…46 The excess adsorption of a binary fluid mixture in a pore with a semipermeable membrane has been investigated by considering the effect of size ratio and volume fraction. 47 Emelyanova et al 14 studied the transmembrane potential of vesicles, which were immersed in an aqueous electrolyte. They observed that adding salt to the electrolyte reversed the sign of the transmembrane potential.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The excess adsorption of a binary fluid mixture in a pore with a semipermeable membrane has been investigated by considering the effect of size ratio and volume fraction. 47 Emelyanova et al 14 studied the transmembrane potential of vesicles, which were immersed in an aqueous electrolyte. They observed that adding salt to the electrolyte reversed the sign of the transmembrane potential.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Researchers have reported the effect of different parameters, such as temperature, mole fraction of the mixture, density, and size ratio on the fluid structure near the membrane . The excess adsorption of a binary fluid mixture in a pore with a semipermeable membrane has been investigated by considering the effect of size ratio and volume fraction . Emelyanova et al studied the transmembrane potential of vesicles, which were immersed in an aqueous electrolyte.…”
Section: Introductionmentioning
confidence: 99%